Eco-evolutionary dynamics in an urbanizing planet. (February 2015) - Alberti, Marina
Highlights Humans mediate eco-evolutionary feedbacks through urbanization. In this review, I discuss studies of observed signatures of urban-driven trait changes across multiple taxa. By linking urban signatures to ecosystem function, we can hypothesize the eco-evolutionary implications of urbanization. The hybrid nature of urban ecosystems is a source of both instability and innovation in the eco-evolutionary dynamic. Understanding the mechanisms by which humans affect eco-evolutionary feedbacks in urban areas will provide new insights for maintaining ecosystem function in an urbanizing planet.